Fine Grinding in a Horizontal Ball Mill - Partyka, Trish; Yan, Denis (Pergamon, 2007)
The fine grinding of ores is increasing due to the depletion of coarse grained, easily processed ore bodies and the increased need to process disseminated, fine grained deposits. The main reason ball mills are not utilised for fine grinding is the perceived poor energy efficiency generally experienced when grinding to fine sizes. However there is a trend towards ball mill grinding for product sizes below the traditional ball mill cut-off of 45 μm. The effect of ball size on the feed and product size distributions in a fine grinding situation was studied. The grinding tests identified a number of trends for fine grinding, including: •Efficient grind curves forming the same shape as for traditional grinding (exponential decay). •The results supporting the claim that fine material is best ground with small media and coarse material with larger media. •The smallest charge was most efficient at treating the finer feeds. •The smaller charges were very ineffective and inefficient for grinding of the coarser feeds. • Efficient grind was undertaken by smaller charges than that recommended by Bond’s ball sizing formula, and • Operating work index analysis confirming the results of the P80-energy analysis.